REKONTRUKSI PEMIKIRAN KH. AHMAD DAHLAN DALAM PENDIDIKAN ISLAM BERKEMAJUAN - Asep Awaluddin; Anip Dwi Saputro (Universitas Muhammadiyah Ponorogo, 2020)
KH. Ahmad Dahlan apart from being a pioneer of modern Islamic education, at the same time proclaimed the principle of combining religious and general sciences. The hustle and bustle of searching for a new format of education in shaping individuals with superior character today needs to see the construction of KH's educational thought. Ahmad Dahlan. This research uses library research method and data analysis uses descriptive content analysis. The result of this research is the need for a reconstruction of KH. Ahmad Dahlan in Muhammadiyah in integrating religious knowledge and general science, namely by adding a content of religious knowledge. Moreover, the meaning of bid'ah still needs to be detailed in the two categories of bid'ah dholalah (bid'ah that are deviant) and bid'ah hasanah (bid'ah that is noble).